Current treatment options for carbon monoxide-induced neurological dysfunction - Dubey, Ayush; Dubey, Shubham (The European Research Journal, 2019)
Carbon monoxide is an established dangerous toxicant with a complex mechanism of cellular toxicity. It is known to cause various neurological symptoms which can manifest both in acute as well as chronic forms. Delayed neurological deficits are often less recognizable. Radiological findings are also less specific. Hyperbaric oxygen therapy has been the mainstay of treatment over the years but is associated with its own list of complications and controversies. Current management for this important condition is discussed here.